Immunomodulatory effects of testosterone and letrozole during Plasmodium berghei ANKA infection - Nolasco-Pérez, Teresita de Jesús; Cervantes-Candelas, Luis Antonio; Buendía-González, Fidel Orlando; Aguilar-Castro, Jesús; Fernández-Rivera, Omar; Salazar-Castañón, Víctor Hugo; Legorreta-Herrera, Martha (Frontiers in Cellular and Infection Microbiology, 2023)
Malaria is one of the main health problems globally. Plasmodium infection causes a pronounced sexual dimorphism, the lethality and severity are greater in males than females. To study the role of testosterone in the susceptibility and mortality of males in malaria, It is common to increase its concentration. However, this strategy does not consider the enzyme aromatase that can transform it into oestrogens. To avoid the interference of these hormones, we inhibited aromatase with letrozole and analysed its impact on the symptomatology and immune response to Plasmodium berghei ANKA infection. We found that administering the combination of letrozole and testosterone to Pb ANKA-infected mice increased the concentration of free testosterone and DHEA but decreased the concentration of 17β-oestradiol. As a result, parasitaemia increased leading to severe anaemia. Interestingly, testosterone increased temperature and decreased glucose concentration as a possible testosterone-mediated regulatory mechanism. The severity of symptomatology is related to important immunomodulatory effects generated by free testosterone; it selectively increased CD8+ T and CD19+ B lymphocyte populations but decreased MAC-3+. Notably, it reduced IL-17 concentration and increased IL-4 and TNF-α. Finally, it increased IgG1 levels and the IgG1/IgG2a ratio. In conclusion, free testosterone plays an important role in pathogenesis in male mice, by increasing CD8+, decreasing MAC3+ and mainly by decreasing IL-17, which is critical in the development of anaemia. Our results are important for understanding the mechanisms that regulate the exacerbated inflammatory response in infectious diseases and would be useful for the future development of alternative therapies to reduce the mortality generated in inflammatory processes